2017
DOI: 10.1007/s00366-017-0511-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of transport property of fibrous media: 3D virtual modeling and permeability calculation

Abstract: work are consistent with the values predicted by the analytical models of layered fiber arrangement proposed by Spielman and Goren. The proposed method thus provides an efficient way of PMFSS design optimization using virtual models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Andersen et al, have shown a clear directional dependence of pressure drop on flow orientation in FeCrAl short-fiber structures [3], and they also identified an analytical model with a good fit when the fluid flow is perpendicular to the isotropic plane [35]. Huang et al [36] calculated the pressure drop based on a length-weighted orientation model. However, the simulation results were not validated appropriately by experimental results.…”
Section: Pressure Drop Of Fiber Structuresmentioning
confidence: 99%
“…Andersen et al, have shown a clear directional dependence of pressure drop on flow orientation in FeCrAl short-fiber structures [3], and they also identified an analytical model with a good fit when the fluid flow is perpendicular to the isotropic plane [35]. Huang et al [36] calculated the pressure drop based on a length-weighted orientation model. However, the simulation results were not validated appropriately by experimental results.…”
Section: Pressure Drop Of Fiber Structuresmentioning
confidence: 99%